Human Resource Development and Employability Skills Training for Sustainable Community Development - Jamaluddin Arief; Varinder Singh Rana; Vüqar Ahmad Mammadli (SocietalServe: Journal of Community Engagement and Services, 2026)
This community engagement program aimed to strengthen community empowerment through human resource development and employability skills training in West Java Indonesia. The program involved youth groups, unemployed individuals, women’s associations, and local community members who experienced limited access to professional training and workforce readiness opportunities. To address these challenges, participatory workshops, leadership training, career mentoring, and collaborative learning activities were implemented over a three-month period involving 65 participants. The findings demonstrated significant improvements in communication skills, teamwork, leadership competencies, career planning awareness, and problem-solving abilities among participants. Qualitative results also revealed increased confidence, stronger motivation for professional development, and greater participation in community and economic activities. Participants showed improved readiness for employment and entrepreneurship opportunities after completing the program. The integration of human resource development and participatory educational approaches proved effective in promoting employability and sustainable community empowerment